Simulasi Kenaikan Tarif Cukai Rokok terhadap Kinerja Ekonomi Rokok di Indonesia - Agustinningtyas, Diska; Agustina, Neli (Jurnal Ekonomi dan Pembangunan Indonesia, 2025)
Production and consumption of cigarettes in Indonesia tend to increase. Increasing production has a positive impact on state revenue. However, the increasing consumption of cigarettes harms public health. The government implemented a policy of cigarette excise tax to control cigarette consumption. This study aims to analyze the impact of increasing the cigarette tax on the economic performance of the cigarette industry. Using Two-Stage Least Squares (2SLS) estimation methods shows that cigarette production is influenced by its consumption. Cigarette consumption is influenced by its price, per capita income in the previous year, and its consumption in the previous year. Cigarette’s price is influenced by its consumption in the previous year, excise tax, and its price in the previous year. The simulation results show that increasing the excise tax by 23 percent is efficient enough to reduce cigarette consumption while still increasing production.